Relationship Between Complications and Quality of Life Among Hemodialysis Patients at a National Hospital in Huancayo, Peru, 2022 - Inga-Romero, Maricruz Elisa (2025)
Introduction: Hemodialysis patients represent a highly vulnerable population, given that the treatment condition alters and modifies their daily interaction with their environment, limiting their activities. Objective: To establish the relationship between post-hemodialysis complications and quality of life in patients in a national hospital in Peru, in the city of Huancayo. Materials and Methods: Quantitative approach and correlational scope, with participation of 140 people by census sampling type, which guaranteed the representativeness of the sample by collecting all the population units that undergo hemodialysis in the Daniel Alcides Carrión Hospital of Huancayo. The SF-36 Health Questionnaire was applied, and a self-report data collection form was used to evaluate post-hemodialysis characteristics such as arterial hypertension, arterial hypotension, nausea, vomiting, headache and cramps. Results: The study found that there is a moderate significant correlation between the variables (p = 0.000; Rho = -0.451), indicating that as patients present greater complications, their perception of quality of life is lower. In addition, significant correlations were found between hemodialysis patient's complications and their physical health (p = 0.000; Rho = -0.479), and mental health (p = 0.000; Rho = -0.366). Conclusions: Higher indicators of post-hemodialysis complications had a negative impact on the perception of quality of life, which underscores the need to develop and program campaigns focused on strengthening quality of life in physical and mental terms to facilitate adherence to treatment.